A five-year review of vertical HIV transmission in a specialized service: cross-sectional study - Hoffmann, Izabel Cristina; Santos, Wendel Mombaque dos; Padoin, Stela Maris de Mello; Barros, Sonia Maria Oliveira de (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Healthcare professionals need to instill the process of prevention, control and treatment of people infected with HIV into care practice. Through maintaining preventive treatment among HIV-infected pregnant women, it has been demonstrated that prophylactic antiretroviral therapy, scheduled cesarean section and the prohibition of breastfeeding significantly reduce vertical HIV transmission. This study aimed to assess the rates of vertical HIV transmission in a specialized service and identify the factors associated with it. DESIGN AND SETTING: Cross-sectional study developed at the University Hospital of Santa Maria (RS), Brazil. METHODS: A cross-sectional study was conducted on a sample of 198 notification forms and medical records of HIV-positive pregnant women and exposed children. RESULTS: The vertical transmission rate was 2.4%, and three children had been infected by vertical HIV transmission. The statistically significant risk factor was the use of injectable drugs. Delayed reporting of pregnancy, absence of antiretroviral therapy during pregnancy, lack of proper prenatal care, incapacity to perform viral load detection tests and CD4+ T cell counts and obstetric and maternal clinical complications were reported. CONCLUSIONS: The vertical transmission rate was high and the recommended intervention measures were not adopted in full. Adequate prophylactic measures need to be implemented in HIV-positive pregnant women prenatally and during the antenatal, delivery and postpartum periods.